Brickwork. Level 1 : for construction diploma and apprenticeship programmes - Thorpe, M. (Malcolm) (London : Routledge, 2021)
Brickwork Level 1 has been adapted from John Hodges's classic Brickwork for Apprentices - the established textbook on brickwork for bricklayers. Designed to meet new requirements of the City and Guilds bricklaying programmes, this book has been written to match the latest industry-based requirements and technical developments in the field, including recent changes to the Building Regulations. Each chapter follows the syllabus and contains a section of multiple-choice questions to provide trainees with vital practice for the job knowledge and multiple-choice tests. Highly illustrated throughout and now in full colour, this is the essential reference for qualified bricklayers and other professionals working in the construction industry, as well as students wishing to embark on a career in bricklaying. There is also the facility to access theSupport Materialon the Routledge website that includes: PowerPoint slides for each chapter Lesson plans and schemes of work Multiple-choice questions and answers Job knowledge questions and answers Practical drawings and mark sheets
OCLC-licensed vendor bibliographic record.
Keywords: Bricklaying; Bricklaying -- Problems, exercises, etc; TECHNOLOGY / Construction / Masonry; TECHNOLOGY / Construction / General; TECHNOLOGY / Construction / Contracting